The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12885-016-2882-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum amyloid A as potential diagnostic marker for lung cancer: a meta-analysis based on nine studies

Abstract: BackgroundPrevious studies have disclosed that serum amyloid A (SAA) is likely involved in the lung cancer pathogenesis and progression. We performed a systematic evaluation and meta-analysis to disclose the correlation between the expression of SAA and lung cancer and to evaluate its value for lung cancer diagnosis.MethodsWe searched the relevant articles from the databases of Medline, Embase, Cochrance Library and Web of Science and calculated the standardized mean difference (SMD) with 95 % confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…Sung et al measured 180 healthy and 170 lung adenocarcinoma plasma or serum samples and found a 14-fold increase of SAA levels in the LC patient [45]. Another by Biaoxue, R. et al indicated that SAA alone could detect LC with 0.59 sensitivity and 0.92 specificity [39]. We measured a six-fold increase in SAA levels at all stages of NSCLC compared to healthy controls.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Sung et al measured 180 healthy and 170 lung adenocarcinoma plasma or serum samples and found a 14-fold increase of SAA levels in the LC patient [45]. Another by Biaoxue, R. et al indicated that SAA alone could detect LC with 0.59 sensitivity and 0.92 specificity [39]. We measured a six-fold increase in SAA levels at all stages of NSCLC compared to healthy controls.…”
Section: Discussionmentioning
confidence: 49%
“…Many of the markers in our set have been studied for decades and have been shown to have potential for diagnosing LC [35][36][37][38][39]. In our studies, certain biomarkers were elevated at higher levels or depressed depending on whether we were looking at early stage (I-II) or late stage (III-IV) NSCLC patients, e.g., the upregulation of CEA and CYFRA-21-1 (common cancer markers widely studied) [36] were not as prominent in early stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, reports from East Asia, Europe and America have shown SAA as a potential diagnostic biomarker for lung cancer having higher specificity for discerning lung cancer but not appropriate for screening because of lesser sensitivity. 17 Results of the present study reveal that SAA levels can be used as a noninvasive biomarker for screening of lung cancer. Our results are at variance from the findings of the metaanalysis that had suggested a better role in distinguishing lung cancer but not for screening in view of a high specificity but lower sensitivity.…”
Section: 16mentioning
confidence: 54%
“…At present, earlystage NSCLC is treated by surgical intervention, while mid-late NSCLC is treated with radiotherapy and chemotherapy. Although effective for some patients in the short run, radiotherapy and chemotherapy are associated with adverse effects, toxicity, high recurrence of tumor and poor prognosis [2]. Therefore, it is necessary to reduce the side effects of chemotherapeutic drugs by searching for more effective anticancer drugs with lower toxicity.…”
Section: Introductionmentioning
confidence: 99%